(3LQjeI GdbJd GdNWC (B: s (3OQGSI ebGQfI (B/ s - (3YHOg eMeO jhSa GdfMGd s; (3ahRjI YHOGdSJGQ Ydis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JSJgOa gPg GdOQGSI GdeYGdLI GdJTQjYjI hGdbGfhfjI dLQjeI GdbJd GdNWC MjK JRGjOJ (B- (3ai GdaJQI GdCNjQI (B- (3MhGOK GdWQb ai cd Ohd GdYGde hGdJi jcef eUOQgG GdQFjSi ai GdEgeGd hGdQYhfI ef bHd GdHYV (B- (3hbO JVefJ gPg GdOQGSI eGgjI GdNWC ZjQ GdYeOi hCfhGYg hJaSjQg hPdc (B- (3ceMhQ CSGSi dgPg GdLQjeI hJfGhdJg GdOQGSI (B( (3abgG hJTQjYG hbVGA (B) (3hGSJYQVJ GdYdGbI GdfaSjI ai JaSjQ hbhY GdNWC hPdc HYQV fXQjGJ KdGK CgegG fXQjI GdNWC YjH ai GdEOGQI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B498-518s
Keywords: (3GdbGfhf GdLfGFjs; (3GdCgeGd hGdQYhfI s; (3fXQjI GdNWhQIs; (3GdbJd GdNWC s; (3aYd GdGYJOGA Ydj GdMjGIs; (3GdYbhHI aj GdJTQjY GdLfGFj GdGSdGejs; (3YbhHI LQjeI GdbJd GdNWCs; (3GdNWC GdeTJQc Hjf eJgejfs; (3GdNWC aj GdbGfhf GdaQfSjs; (3YbhHI GdbJd GdNWC aj UhQJg GdHSjWIs; (3YbhHI GdbJd GdNWC aj UhQJg GdeTOOIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs